Optimization and classification control of permanent basic farmland based on quality classification - Wang, Wei; Chen, Yiling; Liu, Kun; Dang, Yingchun; Li, Guilong; Wen, Liangyou; Cao, Yun (Frontiers in Environmental Science, 2024)
Permanent basic farmland plays an important role in stabilizing agricultural production and ensuring national food security. At present, the country has completed the delineation of 1.55 billion mu of permanent basic farmland, but there is a phenomenon of "not delineating distant farmland, not delineating near farmland, not improving the quality of inferior farmland," and a spatial layout of "far, edge, and scattered farmland". Therefore, how to optimize the spatial layout of permanent basic farmland and achieve graded protection of permanent basic farmland is an urgent scientific problem that needs to be solved. This article is based on the idea of classifying the quality of cultivated land resources, combined with the rules for the delineation of permanent basic farmland, and from the perspective of the synergy of "suitability-connectivitystability" of cultivated land, a indicator system is constructed. Application of suitability, connectivity, and stability evaluation methods. Taking Zhangshu City, Jiangxi Province as an example, the status of cultivated land resources is comprehensively evaluated, and permanent basic farmland is optimized and graded for protection. The major findings and conclusion that the arable land in Zhangshu City is mainly of medium suitability, medium continuity and high stability.Zhangshu City is divided into 43218.80 hm 2 of permanent basic farmland, accounting for 79.35% of the total area of cultivated land. Control and partition permanent basic farmland into three categories: core protected areas for permanent basic farmland, quality improvement areas, and key transformation areas. The above results indicate that this evaluation has a supportive role in supporting the spatial optimization and hierarchical management of permanent basic farmland, and is of great significance for the unified management of natural resources.